Digital Sharia Economic Empowerment at Al-Mukhlisin Islamic Boarding School - Hasibuan, Siti Masitoh; Tolentino, Tolentino (Journal of Islamic Financial Technology, 2025)
This research aims to examine the initiation of a community economic management empowerment model based on sharia at the Al-Mukhlisin Islamic Boarding School with a focus on the economic perspective of the students. Islamic boarding schools, as Islamic educational institutions, have great potential in strengthening the economy of the ummah, particularly through a community-based approach that aligns with sharia principles. This study uses a qualitative method with a case study approach. Data is collected through participatory observation, in-depth interviews, and documentation.The results of the study show that the Islamic boarding school has initiated several sharia-based economic programs such as a cooperative Islamic boarding school, agribusiness units, and entrepreneurship training based on Islamic values. The empowerment model applied leads to the integration of religious education and productive economy, which impacts the enhancement of the economic independence of the Islamic boarding school community. This research recommends strengthening the managerial capacity of the Islamic boarding school and developing more structured sharia economic institutions as a strategic step forward.